How do different amounts of straw as well as compost in the home pen affect the rooting motivation of growing-finishing pigs? - S. Lopez; C. Rufener; M. Holinger (Animal)
Rooting is a strongly motivated, species-specific behaviour of pigs. Most housing systems do not provide appropriate materials that enable the full expression of this behaviour, and it remains unclear whether straw is suitable to entirely fulfil the rooting motivation of pigs. We therefore investigated the suitability of small (minimal) and large (deep) amounts of straw as well as large amounts of compost to satisfy rooting motivation in pigs. Fifty-seven growing-finishing pigs were housed in three pens, each providing permanent access to one of the three treatment substrates. Eight pigs per group were tested individually in a classical preference test (PT) and another eight pigs in a conditioned place preference test (CPPT). In the tests, pigs could show their preference to consume freely available feed (“feed”) or feed hidden in sawdust (“root”). In the CPPT, feed was only present during training but not during testing. Pigs were exposed to the test situation twice, with approximately 72 kg and 115 kg BW. In both tests, the following variables were measured and used as outcome variables in linear mixed effect models: first decision to choose one of the two stimuli (“feed” or “root”), duration of time spent in proximity to “root”, number of changes between stimuli, and latency to the first decision. Overall, the pigs’ first decision (by tendency; P = 0.076) and the duration in proximity to “root” (P = 0.034) varied among treatments: Pigs housed with minimal straw tended to be more likely to choose “root” first (posthoc comparison; P = 0.090) and spent more time in proximity to “root” (P = 0.030) than pigs housed with compost, whereas pigs housed with deep straw were intermediate. Interestingly, the patterns of response to the treatment differed depending on the behavioural tests for both, first decision (interaction; P = 0.032) and duration in proximity to “root” (interaction; by tendency; P = 0.006). In addition, pigs in the PT changed more often between stimuli than pigs in the CPPT (P < 0.001). There was a tendency for an interactive effect between test and treatment for latency to first decision (interaction; P = 0.082), though pairwise comparisons did not reveal any differences. We concluded that in this study housing with permanent access to compost satisfied rooting motivation in pigs more than housing with minimal amounts of straw.